PERSEPSI MAHASISWA AKUNTANSI DALAM MEMILIH KARIR SEBAGAI AKUNTAN PUBLIK PADA UNIVERSITAS NUSANTARA PGRI KEDIRI - Sa’dullah (BAJ: Behavioral Accounting Journal, 2019)
The aim of this research is to test the accounting students’ perception in choosing a career as a public accountant in university of Nusantara PGRI Kediri.This research is based on quantitative used survey method. Technique of collecting data is conducted by interview, questionnaire and observation. Technique of analyzing data in this research used Partial Least Square (PLS).The research findings showed that financial appreciation, professional training, social value, working environment, job vacancy, family and personality has influenced in choosing a career as a public accountant. The result showed that many factors influenced someone in choosing a career as a public accountant.